2016
DOI: 10.1038/srep34546
|View full text |Cite
|
Sign up to set email alerts
|

High expression of MAP7 predicts adverse prognosis in young patients with cytogenetically normal acute myeloid leukemia

Abstract: Microtubule-associated protein 7 (MAP7) plays an important role in cancer cells. In this study, we identified the prognostic significance of MAP7 expression in cytogenetically normal acute myeloid leukemia (CN-AML) patients (aged <60 years) based on several microarray datasets. In the first group (n = 129), high MAP7 expression (MAP7high) was associated with adverse overall survival (OS; P = 0.0441) and event-free survival (EFS; P = 0.0114) compared with low MAP7 expression (MAP7low). In addition, the prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
(52 reference statements)
1
23
1
Order By: Relevance
“…MAPs play a major role in numerous critical cellular and intracellular activities, such as cell division, motility, differentiation and so on ( Bhat and Setaluri, 2007 ). High expression of MAP7 predicts the tumor recurrence and adverse outcomes in colon cancer and is related to a poor prognosis in patients with cytogenetically normal acute myeloid leukemia ( Blum et al, 2008 ; Fu et al, 2016 ). Although the status of AADAC and MAP7D2 and their correlation with prognosis in GC have seldom been reported in the findings from earlier works, they could provide helpful evidence for potential prognostic biomarkers in future studies due to their significance in the nine-gene signature model.…”
Section: Discussionmentioning
confidence: 99%
“…MAPs play a major role in numerous critical cellular and intracellular activities, such as cell division, motility, differentiation and so on ( Bhat and Setaluri, 2007 ). High expression of MAP7 predicts the tumor recurrence and adverse outcomes in colon cancer and is related to a poor prognosis in patients with cytogenetically normal acute myeloid leukemia ( Blum et al, 2008 ; Fu et al, 2016 ). Although the status of AADAC and MAP7D2 and their correlation with prognosis in GC have seldom been reported in the findings from earlier works, they could provide helpful evidence for potential prognostic biomarkers in future studies due to their significance in the nine-gene signature model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of MAP7 in cancers was rarely studied. Studies showed that MAP7 was upregulated in young patients with cytogenetically normal acute myeloid leukemia and predicts poor outcome [13]. The potential function and mechanism of MAP7 in cancer was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The data concerning MAPs in cancer are limited. Up to now, only a few MAPs, including Stathmin-1, EB1, CLIP-170/CLIP1, and some structural MAPs, have been associated with cancerogenesis, outcome prognosis, and chemotherapy sensitivity [268][269][270][271].…”
Section: Microtubule-associated Proteins and Cancermentioning
confidence: 99%